Putting Citizens First: Engagement in Policy and Service Delivery for the 21st Century - A. Lindquist, Evert (ANU Press, 2013)
This book explores the ways in which governments are putting citizens first in their policy-making endeavours. Making citizens the focus of policy interventions and involving them in the delivery and design is for many governments a normative ideal; it is a worthy objective and sounds easy to achieve. But the reality is that putting citizens at the centre of policy-making is hard and confronting. Are governments really serious in their ambitions to put citizens first? Are they prepared for the challenges and demands such an approach will demand? Are they prepared to commit the time and resources to ensure genuine engagement takes place and that citizens' interests are considered foremost? And, more importantly, are governments prepared for the trade-offs, risks and loss of control such citizen-centric approaches will inevitably involve? The book is divided into five parts: - setting the scene: The evolving landscape for citizen engagement - drivers for change: Innovations in citizen-centric governance - case studies in land management and Indigenous empowerment - case studies in fostering community engagement and connectedness - case studies engaging with information technology and new media. While some chapters question how far governments can go in engaging with citizens, many point to successful examples of actual engagement that enhanced policy experiences and improved service delivery. The various authors make clear that citizen engagement is not restricted to the domain of service delivery, but if taken seriously affects the ways governments conduct their activities across all agencies. The implications are enormous, but the benefits to public policy may be enormous too.